The Influence Of Social Media Marketing On The Purchase Of Scarlett Whitening Products On E-Commerce Platforms: Price And Product Quality Analysis - Lili Nova Natalia Br Perangin Angin; Fenny Krisna Marpaung; Dhiva Azzriel Dhinda Shavitry; Dheybie Zelina Situmorang; Juli Meliza (Cita konsultindo, 2024)
Notwithstanding the growing popularity of Scarlett products, there is less understanding of the elements that affect online purchasing behavior. We have found critical elements like product quality, pricing, and social media marketing. This study seeks to investigate the influence of social media marketing initiatives on the acquisition of Scarlett products via e-commerce. This research examines the influence of social media content and user engagement on consumer decision-making. This study investigates the extent to which price significantly influences the purchasing behavior of Scarlett items on e-commerce platforms. This study assesses how customer perceptions about Scarlett product quality affect e-commerce purchase decisions. This quantitative study examined the management student population at Universitas Prima Indonesia who acquired Scarlett whitening goods over the Shopee e-commerce platform. We gathered study data from 100 participants via observation, interviews, and study questionnaires. Data analysis was conducted using SPSS Version 27 software, which included validity testing, accuracy assessment, classical assumptions, multiple regression, and hypothesis evaluation. The results demonstrate that the interplay of price, product quality, and social media promotion affects customers' decisions to buy Scarlett whitening products on e-commerce platforms. In this scenario, the determination test yields an R-Square value of 64.4%, signifying that these factors collectively exert a substantial influence on customer purchase decisions.